MBTI PERSONALITY TYPES for CAREER DEVELOPMENT (SMK Santo Lukas - Jakarta) - Wijaya, Andreas; Novita, Novita; Yulita, Henilia (Jurnal Pengabdian dan Kewirausahaan, 2019)
Indonesia is a pluralistic country with a population of 269 million. Nowadays,it coincide with exploded population faced with unemployment problem. Based on BPS data, in 2018 the  unemployment problem came from high school graduate. This research aim to determine career choices for career planning. The Myers-Briggs Type Indicator (MBTI) is a psychometric personality test that has been widely used to help people choose the career field that best targets the participants are 8th grade students from SMK Santo Lukas North Jakarta, the method psychology through the MBTI test. Measurements were made through questionnaires that contained questions in previous studies with inventory self-report techniques from Cohen for reporting self-condition regarding the lives of one's testicles. The MBTI test was conducted by asking students to obtain a questionnaire, which would then be processed and it is known the personality is then announced with the appropriate type of work. Each result of the questionnaire was submitted and approved, so that all students were satisfied with the learning they had obtained at that time.